Reclaiming Cross-Dressing: Masculinity Construction in the All-Female Yue Opera’s Shakespearean Adaptations - Wu, Yueqi (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
Because it offers the stage such scope for polyerotic interpretation, crossdressing has held an irresistible appeal to theatre practitioners across times and cultures, including Shakespeare in early modern England. The Shakespearean cross-dressing theatre, however, has long excited critical disapprobation as a cultural form which excluded women. However, can cross-dressing as a theatrical device be reclaimed by women as an alternative mode of Shakespearean performance? What academic and practical significance can a reversed, all-female casting of Shakespearean production offer? This paper will argue that the Chinese Yue opera’s Shakespeare adaptations may shed light on how gender impersonation can be used to express women’s wishes and desires. As the second largest Chinese opera genre, Yue opera is a theatreform in which all roles are played by actresses for a predominantly female audience. Interestingly, Shakespeare is also Yue opera’s most adapted foreign playwright. General Ma Long (2001, an adaptation of Macbeth) and Coriolanus and Duliniang (2016, an adaptation of Coriolanus) are two representative specimens of Yue opera Shakespearean adaptations with all-female casting. The male protagonists of both are played by cross-dressed actresses. How do Yue opera female performers, whose style is generally perceived as soft and feminine, stage the Shakespearean war heroes famous for their bloodthirsty masculinity? Deploying a theoretical framework based on Judith Butler’s gender performativity theory and Bertolt Brecht’s account of the epic theatre, this essay aims to examine the masculinity construction in the all-female Yue opera Shakespearean adaptations, in order to open a discussion of how cross-dressing can be used to deconstruct and reassemble gender norms.